Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja pada Pegawai Kecamatan Bekasi Barat - Assyfa Saputrianditha; Hasanuddin Hasanuddin (Journal on Education, 2023)
The purpose of this study was to identify the relationship between employee performance and workplace variables including job satisfaction and stress levels in West Bekasi District. Employees in West Bekasi sub-district were the focus of this study. There were sixty-four people working in this sub-district, and the entire workforce was represented in the sample for the saturated sampling technique. The questionnaire served as the data collection tool for this investigation. For the purpose of conducting these tests, specifically, SPSS version 25 was used for data quality testing, classical assumption testing, multiple linear regression analysis testing, and hypothesis testing. This research utilizes quantitative methodology with data analysis. Based on the t-test results on the data collected for this study, the work environment in West Bekasi Sub-district has a positive impact on staff performance. This finding is supported by the fact that the number 6.064 is greater than 1.999. Meanwhile, the findings from the t-test show that the work stress variable has a positive and statistically significant effect on staff performance in West Bekasi Sub-district, with a score of 8,000 higher than the score of 1,999. Findings from the data analysis conducted using the F test show that the work environment and the amount of work-related stress both have a favorable and significant impact on overall employee performance in West Bekasi Sub-district. The F test result is 238.513 > 3.15, and the R² test shows that 88.7% of the correlation that occurs between the two variables.